2022
DOI: 10.1111/dom.14810
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of DBPR108 (prusogliptin) as an add‐on to metformin therapy in patients with type 2 diabetes: A 24‐week, multi‐centre, randomized, double‐blind, placebo‐controlled, superiority, phase III clinical trial

Abstract: Aim: To evaluate the efficacy and safety of DBPR108 (prusogliptin), a novel dipeptidyl peptidase-4 (DPP-4) inhibitor, as an add-on therapy in patients with type 2 diabetes (T2D) that is inadequately controlled with metformin. Materials and Methods:In this 24-week, multi-centre, randomized, double-blind, placebo-controlled, superiority, phase III study, adult T2D patients with HbA1c levels ranging from 7.0% to 9.5% on stable metformin were enrolled and randomized (2:1) into the DBPR108 + metformin and placebo +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…The magnitude of HbA1c reduction relative to the placebo achieved with DBPR108 100 mg in our study was similar to that observed in other studies with DBPR108 20,21 and in other DPP-4…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The magnitude of HbA1c reduction relative to the placebo achieved with DBPR108 100 mg in our study was similar to that observed in other studies with DBPR108 20,21 and in other DPP-4…”
Section: Discussionsupporting
confidence: 91%
“…20 In addition, a 24-week randomized double-blind trial, comparing the safety and efficacy of DBPR108 plus metformin to placebo plus metformin in patients with uncontrolled type 2 diabetes, revealed a significantly greater reduction in HbA1c with DBPR108 100 mg plus metformin compared with placebo plus metformin [À0.70% (0.09%) vs. À0.07% (0.11%)]. 21 Two phase 3 multicentre, randomized, double-blind, placebo-controlled trials (including the present study) and one phase 2 multicentre, randomized, double-blind, placebo-controlled, multiple-dose trial have been successfully completed. Currently, DBPR108 is undergoing a new drug application process with the National Medical Products Administration (NMPA) for the treatment of type 2 diabetes, underscoring its potential as a pivotal therapeutic intervention in this domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worth noting that many clinical studies that used DPP-4 inhibitors also adopted a 24-week treatment duration and obtained meaningful results. 14,47,48 Third, echocardiography was used in this study rather than cardiac MRI, which is a more advanced technique that provides more detailed information about the heart muscle and blood flow. However, echocardiography is a more widely available and cost-effective technique that is useful for the evaluation of the structure and function of the heart valves and chambers.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the 24‐week duration of the study may not have been sufficient to confirm the long‐term cardiovascular safety of the drug. However, it is worth noting that many clinical studies that used DPP‐4 inhibitors also adopted a 24‐week treatment duration and obtained meaningful results 14,47,48 . Third, echocardiography was used in this study rather than cardiac MRI, which is a more advanced technique that provides more detailed information about the heart muscle and blood flow.…”
Section: Discussionmentioning
confidence: 99%